The influence of ripeness stage and growth area on myrtle-leaved orange (chinotto) peel essential oil composition. (August 2020) - Flamini, Guido; Pistelli, Laura; Ascrizzi, Roberta; Pistelli, Luisa; Zinnai, Angela
Abstract: Myrtle-leaved orange, or chinotto, is a Chinese lesser-known citrus, nowadays cultivated in all the Mediterranean area of Italy. Its fruits are traditionally used in the confectionary and beverage industries: the former mainly uses the unripe fruits, while the juice of the ripe ones is the core ingredient of the well-known Italian soft drink "Chinotto". In the present work, the compositions of several accessions of chinotto fruit peel essential oils (EOs) have been analysed by GC-MS: in particular, i) fresh specimens from Savona (Liguria, Italy) at different ripening stages, as well as a dried ripe one; ii) two accessions from Pisa (Tuscany, Italy), of which one native and one transplanted from Savona. A comparison of the analysed samples with literature reported EO compositions has been performed by means of multivariate statistical analysis. The aim was to assess the influence of both the ripening stage and the geographical area of collection on the EO, assessing which factor influenced it the most. The ripening stage influence on the EO composition was found to be less significant compared to the geographical area of growth of the specimens. The statistical analyses, indeed, evidenced a proximity in the compositions obtained from the different ripening stages, whereas greater differences were evidenced for samples at the same ripening phase, but coming from different regions. Graphical abstract: Image 1 Highlights: The influence of provenience and ripening on Chinotto EO composition was evaluated. The results were compared to published studies to broaden the sampling population. Analytical methods and chemometrics were coupled to evidence existing patterns. The most influencing parameter was the geographical area of origin of the specimen. The ripening stage was less impacting on the EO compositions from the same area.